2017
DOI: 10.3892/mmr.2017.8201
|View full text |Cite
|
Sign up to set email alerts
|

Samchuleum attenuates diabetic renal injury through the regulation of TGF‑β/Smad signaling in human renal mesangial cells

Abstract: Renal mesangial cell proliferation is a major clinical feature of diabetic nephropathy (DN) and includes glomerulosclerosis and renal fibrosis. Samchuleum (SCE) is a traditional herbal mixture that is recorded in the ancient Korean medical book, Donguibogam. The present study attempted to determine whether SCE treatment was able to improve high glucose (HG)‑induced mesangial cell fibrosis and glomerulosclerosis in primary cultured human mesangial cells. Thymidine incorporation under HG induction was increased,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…TGF-β1 plays an important role in cell proliferation. After TGF-β1 binds to the serine/threonine kinase receptor on the surface of mesangial cells, the signal is transferred from the cell membrane to the nucleus mediated by Smad proteins (34,35). In the present study, TGF-β1 was used to induce HMc proliferation.…”
Section: Discussionmentioning
confidence: 87%
“…TGF-β1 plays an important role in cell proliferation. After TGF-β1 binds to the serine/threonine kinase receptor on the surface of mesangial cells, the signal is transferred from the cell membrane to the nucleus mediated by Smad proteins (34,35). In the present study, TGF-β1 was used to induce HMc proliferation.…”
Section: Discussionmentioning
confidence: 87%
“…Transforming growth factor-β1 (TGF-β1) is an important promoting fibrosis factor, which mediates renal fibrosis and glomerulosclerosis. Continuous hyperglycemia can produce TGF-β1 by stimulating the kidney of DN, which increases the expression and secretion of extracellular matrix protein (ECM) and leads to renal fibrosis (Hills et al, 2018 andYoon et al, 2018). This study showed that the expression of protein TGF-β1 was significantly increased in renal tissue of DN.…”
Section: Discussionmentioning
confidence: 90%
“…Although in the case of CB, there have been no reports of specific antibacterial effects, its anti-inflammatory effects associated with inhibition of the iNOS synthesis pathway may contribute to suppressing the cytokine storm induced in response to bacterial invasion. PS and CR extracts also exert an anti-fibrotic effect by suppressing TGF-β expression [29,30]. It has also been suggested that these two constituents may inhibit excessive fibrosis subsequent to ulcerative healing by suppressing the production of TGF-β.…”
Section: Discussionmentioning
confidence: 99%